Find Us On: Facebook Twitter Rss Feed Blog
Need To Register? Sign Up Login

CALCULUS AB EXAM--INVERSE, DERIVATIVES

billfeinberg
billfeinberg 


F(x) = x^3-x-6 G(x) is the inverse of F(x) Find: F'[G(0)][G'(0)] Attachments
Tags Clarifications

Answers

CALCULUS AB EXAM--INVERSE, DERIVATIVES

billfeinberg
billfeinberg 



Find: f'[g(0)][g '(0)]

Let g(0)=x which means f(x)=0, or, x^3-x-6=0. This equation is true if the terms involving x add up to 6; this happens if x=2. So g(0)=2, f(2)=0, and f '(x) = 3x^2-1

Since f...
Attachments
Screenshots
Purchase Answer